Integration of the balanced scorecard framework and analytical hierarchical procedure to determine the performance assessment model of public sector organizations - Ayunda Putri Nilasari; Retnosari Retnosari; Diah Agustina Prihastiwi; Yulida Army Nurcahya (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
Measurement of organizational performance is a complex problem because of the many factors that affect performance. In addition, each organization must have different contingency conditions and managerial priorities that are not the same and can even conflict with each other. This research is exploratory, which aims to develop a performance measurement model in government organizations that have the main function of serving the community. The preparation of performance measurement models in public organizations using the Balanced Scorecard (BSC) and Analytic Hierarchy Process (AHP) framework. The data used in this study are qualitative and quantitative data obtained through interviews, focus group discussions (FGD), and questionnaire instruments. The sample of this research is the employees of Mertoyudan District, Bandongan District, Salaman District, and Tempuran District. The object of research is asked to sort the performance measures that have been compiled from the most relevant to the least relevant. The results of the analysis were then analyzed using SEM. From the results of the study it can be concluded that the performance measurement at the Magelang district office using the Balanced Scorecard Method and weighting with Analytical Hierarchy Processes (AHP) overall, the competence at the Magelang district office is quite good. and from all perspectives measured, the customer perspective has the largest weighting is 0.483, the second is 0.272, the third is the internal business process perspective is 0.157 and the last is growth and learning 0.088.